2016
DOI: 10.1177/0706743716673320
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the French Version of the DSM-5 Yale Food Addiction Scale in a Nonclinical Sample

Abstract: Objective: The Yale Food Addiction Scale (YFAS) is the only questionnaire that assesses food addiction (FA) based on substance dependence criteria in the Diagnostic and Statistical Manual of Mental Disorders (DSM), Fourth Edition, Text Revision. Following recent updating of addiction criteria, a new DSM-5 version (YFAS 2.0) has been developed. Our study tested the psychometric properties of the French YFAS 2.0 in a nonclinical population. Method:We assessed 330 nonclinical participants for FA (French YFAS 2.0)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
3
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 39 publications
5
58
3
6
Order By: Relevance
“…Specifically, scores on the dYFAS-C 2.0 were positively associated with emotionally and externally triggered consumption, constructs also implicated in SUDs (Joyner et al, 2015;Loxton & Tipman, 2017;Manzoni et al, 2018). Prior food addiction research in adults and children with other versions of the YFAS have found similar associations with emotional and externally triggered eating (Brunault et al, 2017;Clark & Saules, 2013;Gearhardt et al, 2009Gearhardt et al, , 2016Loxton & Tipman, 2017;Manzoni et al, 2018). These findings suggest that interventions to increase emotion regulation (e.g., mindfulness) and the ability to cope with environmental triggers (e.g., craving management) may be beneficial for adolescents endorsing indicators of food addiction, although future research is needed.…”
Section: Discussionmentioning
confidence: 95%
“…Specifically, scores on the dYFAS-C 2.0 were positively associated with emotionally and externally triggered consumption, constructs also implicated in SUDs (Joyner et al, 2015;Loxton & Tipman, 2017;Manzoni et al, 2018). Prior food addiction research in adults and children with other versions of the YFAS have found similar associations with emotional and externally triggered eating (Brunault et al, 2017;Clark & Saules, 2013;Gearhardt et al, 2009Gearhardt et al, , 2016Loxton & Tipman, 2017;Manzoni et al, 2018). These findings suggest that interventions to increase emotion regulation (e.g., mindfulness) and the ability to cope with environmental triggers (e.g., craving management) may be beneficial for adolescents endorsing indicators of food addiction, although future research is needed.…”
Section: Discussionmentioning
confidence: 95%
“…Forty-four of the 51 studies utilised the standard version of the YFAS, of which six had been converted to and validated in the following non-English languages: Italian (n = 6) (20,40,(51)(52)(53)(54) , French (n = 3) (36)(37)(38) , German (n = 3) (15,64,67) , Spanish (n = 4) (17,49,50,73) , Arabic (n = 1) (76,82) , Chinese (n = 1) (42) and Turkish (n = 1) (71) . Three studies used the shorter version of the YFAS, referred to as the modified YFAS (mYFAS), which comprises nine questions rather than the standard 25 items (45,60,72) ; these studies were larger populationbased surveys.…”
Section: Food Addiction Outcomesmentioning
confidence: 99%
“…One study by Flint et al (45) used both versions of the YFAS and found the prevalence of FA to be lower (9%) when using the shortened tool (mYFAS) compared to the full-length version (11.4%). Two studies used the YFAS-Children version and five studies used the revised YFAS 2.0 tool (8,15,38,43,67) , which has also been converted to both French (38) and German (15,67) .…”
Section: Food Addiction Outcomesmentioning
confidence: 99%
“…The concept of food addiction (FA) continues to gain attention, with recent interest directed towards understanding the cross-cultural presentation of FA symptomology and clinical correlates (Brunault et al, 2017;Chen, Tang, Guo, Liu, & Xiao, 2015). The FA model posits that certain individuals are susceptible to a patterned addictive response to highly palatable foods, which reinforces problematic eating behaviour (Gearhardt, Davis, Kuschner, & Brownell, 2011).…”
Section: Introductionmentioning
confidence: 99%